Oxygen evolution on well-characterized mass-selected Ru and RuO2 nanoparticles. Issue 1 (2nd October 2014) - Paoli, Elisa A.; Masini, Federico; Frydendal, Rasmus; Deiana, Davide; Schlaup, Christian; Malizia, Mauro; Hansen, Thomas W.; Horch, Sebastian; Stephens, Ifan E. L.; Chorkendorff, Ib
Abstract : Well-defined mass-selected Ru and RuO2 nanoparticles exhibit an order of magnitude improvement in the oxygen evolution activity, relative to the state-of-the-art, with a maximum at around 3–5 nm. Abstract : Oxygen evolution was investigated on model, mass-selected RuO2 nanoparticles in acid, prepared by magnetron sputtering. Our investigations include electrochemical measurements, electron microscopy, scanning tunneling microscopy and X-ray photoelectron spectroscopy. We show that the stability and activity of nanoparticulate RuO2 is highly sensitive to its surface pretreatment. At 0.25 V overpotential, the catalysts show a mass activity of up to 0.6 A mg −1 and a turnover frequency of 0.65 s −1, one order of magnitude higher than the current state-of-the-art.